La majorité oubliée: le rôle des femmes à Montréal au 19e siècle - Cross, D. Suzanne (Les femmes dans la société québécoise, 1977)
Keywords: Femmes

Historiennes engagées et femmes patriotes: la révolution de 1837-1838 et la place des femmes dans l'histoire du Québec - Arsenault, Mathieu (Profession historienne? Femmes et pratique de l’histoire au Canada français, XIXe-XXe siècles, 2023)
Keywords: Femmes; Histoire; Rébellions

L'histoire des femmes au Québec depuis quatre siècles - Collectif Clio (Le Jour, 1992)
Keywords: Femmes

Les femmes patriotes: de la réalité à la fiction - Aubin, Georges (Bulletin d'histoire politique, 2003)
Keywords: Femmes; Rébellions

Les femmes et le vote au Bas-Canada, 1791-1849 - Picard, Nathalie (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Élections

1810-1895: l’entrée des femmes dans l’arène sportive - Janson, Gilles (Cap-aux-Diamants, 2013)
Keywords: Femmes; Patin

Les femmes et le vote au Bas-Canada de 1792 à 1849 - Picard, Nathalie (Université de Montréal, 1992)
Keywords: Femmes; Élections

Rhétorique et autoreprésentation: la pratique épistolaire des femmes en temps d'insurrections - Bédard, Mylène (Université de Laval, 2014)
Keywords: Femmes; Écrivains

Écrire en temps d'insurrections: pratiques épistolaires et usages de la presse chez les femmes patriotes (1830-1840) - Bédard, Mylène (Presses de l'Université de Montréal, 2016)
Keywords: Femmes; Écrivains

Oubliées de l'histoire officielle. Les femmes du marché Sainte-Anne - Poutanen, Mary Anne; Olson, Sherry (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

Le travail des femmes célibataires de l'élite et la famille pendant la période préindustrielle à Montréal - Fortin, Jonathan (L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles, 2019)
Keywords: Famille; Femmes; Fourrure; Marchands; Travail

Rire après les Rébellions: les femmes comme miroir déformant de l’actualité canadienne dans Le Fantasque de Napoléon Aubin - Bédard, Mylène (Mens, 2018)
Keywords: Aubin, Napoléon; Femmes; Humour; Journalistes; Rébellions

« Se soumettre de bon coeur à son mari »: le combat d'une femme face à l'autoritarisme marital - Lamonde, Yvan (Presses de l'Université Laval, 2022)
Keywords: Avocats; Doutre, Joseph; Femmes; Guibord, Joseph; Institut canadien; Mariage; Renaud, Marie-Zoé-Aimée; Trudel, François-Xavier-Anselme; Ultramontains

"Due Attention Has Been Paid to All Rules": Women, Tavern Licences, and Social Regulation in Montreal, 1840–1860 - Poutanen, Mary Anne (Histoire sociale / Social History, 2017)
Keywords: Femmes

Women and Technological Change in Nineteenth Century Montreal - Bradbury, Bettina (Women, Work and Place, 1994)
Keywords: Femmes

Quebec Women: a History - Collectif Clio (Women's Press, 1987)
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in 19th Century Montreal - Cross, D. Suzanne (The Canadian City. Essays in Urban History, 1977)
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in Nineteen Century Montreal - Cross, D. Suzanne (The Social Development of Canada - Readings, 1983)
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in 19th Century Montreal - Cross, D. Suzanne (The Neglected Majority: Essays in Canadian Women's History, 1977)
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in 19th Century Montreal - Cross, D. Suzanne (Histoire sociale / Social History, 1973)
Keywords: Femmes

"A Most Detestable Crime": Gender Identities and Sexual Violence in the District of Montreal, 1803-1843 - Ramos, Sandy (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2001)
Keywords: Femmes

Inventories, Interiors, and Women’s Ambitions: Strategies of Property Ownership in Three Mid-19th Century Montreal Public Houses - Poutanen, Mary Anne (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Femmes

Working Families: Age, Gender and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Labour / Le travail, 1994)
Keywords: Famille; Femmes

L'histoire des Montréalaises: un chantier en construction - Baillargeon, Denyse (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Femmes; Histoire

Le leadership féminin dans les associations privées de charité protestantes au XIXe siècle à Montréal - Harvey, Janice (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Protestants

William Notman’s Portrait Photographs of the Wealthy English-speaking Girls of Montreal: Representations of Informal Female Education in Relation to John Ruskin’s “Of Queens’ Gardens” and Writings by and for Canadians from the 1850s to 1890s - Lerner, Loren Ruth (Revue d'histoire de l'éducation / Historical Studies in Education, 2009)
Keywords: Bourgeoisie; Femmes

Widows Negotiate the Law: The First Year of Widowhood in Early-Nineteenth-Century Montreal - Bradbury, Bettina (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: Femmes; Veuvage

Wife to Widow: Lives, Laws, and Politics in Nineteenth-Century Montreal - Bradbury, Bettina (University of British Columbia Press, 2011)
Keywords: Femmes; Veuvage

Bonds of Friendship, Kinship, and Community: Gender, Homelessness, and Mutual Aid in Early-Nineteenth-Century Montreal - Poutanen, Mary Anne (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: Femmes; Itinérance

Widows at the Hustings: Gender, Citizenship, and the Montreal By-Election of 1832 - Bradbury, Bettina (Women on their Own. Interdisciplinary Perspectives on Being Single, 2008)
Keywords: Femmes; Élections

Teachers, Gender, and Bureaucratizing School Systems in Nineteenth Century Montreal and Toronto - Danylewycz, Marta; Prentice, Alison Leeds (History of Education Quarterly, 1984)
Keywords: Enseignants; Femmes

Working Families: Age, Gender, and Daily Survival in Industrializing Montreal - Bradbury, Bettina (McClelland & Stewart, 1993)
Keywords: Famille; Femmes

Women at the Hustings: Gender, Citizenship, and the Montreal By-Elections of 1832 - Bradbury, Bettina (Rethinking Canada: the Promise of Women’s History, 2011)
Keywords: Femmes; Élections

Beyond Brutal Passions. Prostitution in Early Nineteenth-Century Montreal - Poutanen, Mary Anne (Study on the History of Quebec/Études d'histoire du Québec, 2015)
Keywords: Femmes; Prostitution

Une histoire sociale de la prostitution: Montréal, 1800-1850 - Poutanen, Mary Anne (Les éditions du remue-ménage, 2021)
Keywords: Femmes; Prostitution

Charivari, libéralisme et genre au Bas-Canada, 1820-1860 - Cournoyer, Amy (Université du Québec à Trois-Rivières, 2020)
Keywords: Femmes; Libéralisme

Liens d’amitié, de parenté et d’appartenance à une collectivité : genre, itinérance et aide mutuelle à Montréal au début du XIXe siècle - Poutanen, Mary Anne (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Femmes; Itinérance

Veuves et électrices : genre, citoyenneté et élection partielle à Montréal en 1832 - Bradbury, Bettina (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Femmes; Élections

Les vocations féminines de la région montréalaise au XIXe siècle - Payette, Céline (Université du Québec à Montréal, 1991)
Keywords: Communautés religieuses; Femmes

« La force, la grâce, la souplesse »: l’éducation physique des jeunes filles canadiennes-françaises à Montréal (1860-1920) - St-Georges, Valérie (Université de Montréal, 2019)
Keywords: Femmes; Éducation physique

Women and Wage Labour in a Period of Transition, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1987)
Keywords: Famille; Femmes; Travail

Class, Culture, Family and the Law: Wife to Widow in Nineteenth-Century Quebec - Bradbury, Bettina (Programme d'études sur le Québec de l'Université McGill, 1997)
Keywords: Femmes; Mariage; Veuvage

The Evolution of the Sexual Division of Labour in Teaching: A Nineteenth-Century Ontario and Quebec Case Study - Danylewycz, Marta (Histoire sociale / Social History, 1983)
Keywords: Enseignants; Femmes; Travail

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Histoire sociale / Social History, 1984)
Keywords: Famille; Femmes; Travail

"Against her Will and without her Consent": Women, Sexual Crimes and the Law in the District of Montreal, 1803-1843 - Ramos, Sandy (Université Concordia, 1996)
Keywords: Criminalité; Droit; Femmes

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail

Shelter from the Hurry? Hospitality in Montreal, 1836-1913 - Poutanen, Mary Anne; Olson, Sherry (Architectures of Hurry - Mobilities and Modernity in Urban Environments, 2018)
Keywords: Auberges; Femmes; Hôtellerie

Histoire d’un système judiciaire à plusieurs vitesses: analyse intersectionnelle des procès pour meurtre dans la juridiction de Montréal entre 1700 et 1760 - Berthelet, Marie-Ève (Université de Montréal, 2019)
Keywords: Autochtones; Criminalité; Femmes

"Every Attention Will Be Paid to the Satisfaction of the Guests": Angélique Archambault and Donegana’s Hotel, 1852-1864 - Poutanen, Mary Anne (Sharing Spaces: Essays in Honour of Sherry Olson, 2020)
Keywords: Femmes; Hôtellerie; Mariage

Female Authorship, Incomplete Archives, and the Periodical Press in Nineteenth Century Montreal: The Case of Rosanna Mullins Leprohon - Cabajsky, Andrea (Port Acadie, 2022)
Keywords: Archives; Femmes; Écrivains

Robertine Barry, On l’appelait Monsieur - Desjardins, Sergine (Histoire Québec, 2024)
Keywords: Femmes; Journalistes; Patrie (La)

Domaine des soeurs grises de Montréal - Gauthier, Raymonde (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Femmes; Patrimoine; Soeurs Grises

The Homeless, the Whore, the Drunkard, and the Disorderly: Contours of Female Vagrancy in the Montreal Courts, 1810-1842 - Poutanen, Mary Anne (Gendered Pasts: Historical Essays in Femininity and Masculinity in Canada, 1999)
Keywords: Délinquance; Femmes; Itinérance; Prostitution

The Development of Higher Education for Women at McGill University from 1857 to 1899 with Special Reference to the Role of Sir John William Dawson - Ronish, Donna Ann (Université McGill, 1972)
Keywords: Dawson, William; Femmes; Université McGill

Public Houses and Hidden Networks: Roles of Women in Mid-Nineteenth-Century Montreal - Poutanen, Mary Anne; Olson, Sherry (Micro-Geographies of the Western City, c.1750-1900, 2020)
Keywords: Auberges; Famille; Femmes; Hôtellerie

Recovering Identities from the Judicial Archives of Quebec - Olson, Sherry; Poutanen, Mary Anne (Histoire sociale / Social History, 2024)
Keywords: Archives; Enfants; Famille; Femmes

Intimacies in the Neighbourhood: Revisiting Sex Commerce, Families, and Criminal Court Records in Early Nineteenth-Century Montreal - Poutanen, Mary Anne (Family and Justice in the Archives. Historical Perspectives on Intimacy and the Law, 2024)
Keywords: Criminalité; Famille; Femmes; Prostitution

Left Out of the Official History. The Women of St Anne's Market - Poutanen, Mary Anne; Olson, Sherry (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

La tutelle des enfants mineurs au Bas-Canada: autorité domestique, traditions juridiques et masculinités - Garneau, Jean-Philippe (Revue d'histoire de l'Amérique française, 2021)
Keywords: Enfants; Famille; Femmes; Mariage; Veuvage

Les seigneuresses de l'île - Barthe, Marcel (Les Argoulets, 2024)
Keywords: Congrégation de Notre-Dame; Femmes; Île-des-Soeurs

Their benevolant design: conervative women and protestant child charities in Montreal - Harvey, Janice (McGill-Queen's University Press, 2024)
Keywords: Enfants; Femmes; Montreal Ladies' Benevolent Society; Protestants

Taking the Veil in Montreal, 1840-1920: An Alternative to Marriage, Motherhood and Spinsterhood - Danylewycz, Marta (Université de Toronto, 1981)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Femmes; Soeurs de Miséricorde

Taking the Veil: An Alternative to Marriage, Motherhood, and Spinsterhood in Quebec, 1840-1920 - Danylewycz, Marta (McClelland and Stewart, 1987)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Femmes; Soeurs de Miséricorde

Le Club des archères de Montréal existait-il réellement? - Martin, Gabriel (Histoire Québec, 2020)
Keywords: Clubs; Femmes; Histoire; Montreal Ladies Archery Club / Montreal Archery Club

On ne naît pas mère, on le devient : le parcours de Julie Papineau - Smart, Patricia (De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime, 2014)
Keywords: Famille; Femmes; Mariage; Papineau (famille); Papineau, Louis-Joseph; Rébellions

De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime - Smart, Patricia (Essais et Documents, 2014)
Keywords: Dessaulles, Henriette (Fadette); Famille; Femmes; Le Normand, Michelle; Marchand-Dandurand, Joséphine; Mariage; Papineau (famille); Rocbert de La Morandière, Élizabeth (Bégon, Élizabeth)